Gold nanoparticles for plasmid delivery - Almeida, Ana Catarina Couto (2014)
Gene therapy presents an ideal strategy for the treatment of genetic as well as acquired diseases, such as cancer and typically involves the insertion of a functioning gene into cells to correct a cellular dysfunction or to provide a new cellular function. Gene delivery vectors are based in two models: viral and non-viral. Viral vectors have high transfection efficiency but their major barrier is immunogenicity. Since the non-viral vectors have no immunogenicity, these have been widely studied. Gold nanoparticles have been proposed as optimal delivery systems of genetic material, due their small size, high surface-to-volume ratio and the ability to be functionalized with multiple molecules. In the present work, an AuNP-based formulation was developed to deliver a plasmid in a colorectal cancer cell line, containing as reporter gene the gene encoding to EGFP. The delivery system resulted from the functionalization of 14 nm AuNP with a PEG layer (4300114 PEG chains/AuNP), which increases stability and biocompatibility of AuNPs; quaternary ammonium groups which provide positive charges that allow electrostatic binding of plasmid, which is considered the therapeutic agent to be transported into cells. The system developed was characterized by UV-vis spectroscopy, DLS, TEM and by electrophoretic mobility, yielding a formulation with 113.5 nm.Transfection efficiency of the formulation developed was evaluated through PCR and through EGFP expression by fluorescence microscopy and fluorescence spectroscopy. The internalization was observed 3h post transfection; however a low level of EGFP expression was achieved. After 24h of incubation, EGFP expression increases just 3 times compared to non-transfected cells. The commercial system (Lipofectamine) expressed EGFP 5 times more than the system developed AuNP@PEG@R4N+@pEGFP. This difference could be related to lower translocation to the nucleus.